Karakterisasi Sifat Magnetik Daun Untuk Analisa Polusi Udara: Sebuah Tinjauan Ulang - Yulia Widia Sari; Yeggi Darnas; Abd. Mujahid Hamdan (Fakultas Teknik, 2020)
Air pollution is one of the environmental problems that can have serious impacts on humans and the environment. To prevent these negative impacts from spreading, environmental monitoring efforts can be carried out periodically. The existing monitoring methods basically use chemical methods that are destructive. Therefore, the development and use of fast and non-destructive methods is a much-needed innovation. One of the alternative methods that are expected to be such an innovation is the rock magnetization method. Magnetic rocks have been used to assess climate and environmental changes. The application of this method has been used in the field of biomagnetism or the study of magnetism in living things through the presence of magnetic minerals based on the type, grain size, grain shape, and morphology. This article is an overview of the use of rock magnetization methods to characterize leaves as receptors for atmospheric pollutants.